Factors Effecting the Success of Community Service Business in Pattaya City, Chonburi Province - ตั้งเอกชัย กำพล (Community and Social Development Journal, 2016)
The objectives of this research paper were 1) to study the context of the Community Service Business in Pataya City, Chonburi province and 2) to study the factors that affect the success of the Community Service Business in Pataya City, Chonburi province. The samples were of community leaders and individuals who involved with the Community Service Business in Pataya City 40 people by specific method. The research tools include the questionnaire and the structured interviews. The research found that : Most were the member of the Community Service Business more than two years (50.00%). Most have work done (57.50%). Most have moderate debt (82.50%). Never established Community Service Business (52.50%). They have interested to cooperate with the activities of the Community Service Business (60.00%). They want to participate in the activities of the Community Service Business, have confident in the integration of Community Service Business. They can tell the details about the Community Service Business that correctly. The Community Service Business have adequate capital to operate, They think the Community Service Business sufficient market demand. Ever get support tools. The member of Community Service Business have increased revenue from this business venture, and the lives were better more than ever. They think the product were development regularly. The effective productivity and they think the operation achieve the purpose (100.00%). The 9 factors affect that to the success of the Community Service Business in Pataya City, Chonburi Province.